SAMPAH LAUT: ULASAN PENCEMARAN LINGKUNGAN - Ika Kusumawati (JURNAL PERIKANAN TROPIS, 2016)
Man-made debris exist in every ocean and contaminate marine habitats. Solid materials, typically waste, that has found its way to the marine environment is called marine debris. Composed largely of plastics, marine debris can include cigarette filters, baby diapers, automobiles, six-pack rings, beverage bottles and cans, disposable syringes, plastic bags, bottle caps, fishing line and gear, and thousands of other objects. Plastic items are the most abundant type of marine debris on a global scale and plastic is also the most frequently reported material in encounters between debris and marine organisms. There are various sources of marine debris from activities both on land and at sea. Land-based sources include littering, losses from plastic manufacturing plants, landfills and storm drains.While sea-based sources include fishing gear, garbage from shipping and recreational boats, offshore drilling platforms and rigs. Marine debris is more than an unsightly inconvenience for beach-bound vacationers or pleasure boaters. It also affects the inhabitants and economies of coastal and waterside communities worldwide. In addition to the increasingly well-recognised problems that marine debris causes to the environment, coastal communities and marine industries, there is now compelling evidence of the large-scale and serious threat that it poses to the welfare of wild marine animals. The resulting poor welfare, outlined and summarised in this report, creates a compelling argument that marine debris must be viewed not only as a serious environmental, conservation, human health and economic issue, but also as a significant global animal welfare issue that requires urgent action.